The Urgency of Reconstructing the Regulation of Medical Dispute Resolution as a Form of Legal Protection for the Dental Profession in Indonesia from the Perspective of the Philosophy of Legal Positivism in Indonesia - M. Natsir Asnawi; Rika Noviantini; Imas Naeni; Fuji Utomo (Dinasti Research, 2025)
This research explores the urgency of reconstructing the regulations on the resolution of medical disputes as a form of legal protection for dental professionals in Indonesia, viewed through the lens of legal positivism philosophy. Medical disputes present significant challenges to dental practitioners, necessitating a robust legal framework to safeguard their professional interests. The study aims to analyze the regulatory mechanisms governing medical dispute resolution, focusing on their role in protecting the rights and legal obligations of dental professionals. Utilizing a normative juridical approach, this research examines existing laws and regulations related to medical dispute resolution in Indonesia, alongside relevant literature. By elucidating the reconstruction of these regulatory frameworks, the study discusses their effectiveness in protecting the legal interests of dental professionals. These findings are expected to provide a deeper understanding of the urgency of reconstructing the regulations on medical dispute resolution in Indonesia from the perspective of legal positivism philosophy, thereby contributing to the enhancement of legal protection for dental professionals and the improvement of professional standards in dental practice.